The Role of PPARα Activation in Liver and Muscle - Lena Burri; G. Hege Thoresen; Rolf K. Berge (PPAR Research)
PPARα is one of three members of the soluble nuclear receptor family called peroxisome proliferator-activated receptor (PPAR). It is a sensor for changes in levels of fatty acids and their derivatives that responds to ligand binding with PPAR target gene transcription, inasmuch as it can influence physiological homeostasis, including lipid and carbohydrate metabolism in various tissues. In this paper we summarize the involvement of PPARα in the metabolically active tissues liver and skeletal muscle and provide an overview of the risks and benefits of ligand activation of PPARα, with particular consideration to interspecies differences.